Heterologous Expression and Characterization of a High-Efficiency Chitosanase From Bacillus mojavensis SY1 Suitable for Production of Chitosan Oligosaccharides - Wang, Jianrong; Li, Xiaoming; Chen, Hao; Lin, Bilian; Zhao, Liangzhong (Frontiers in Microbiology, 2021)
Chitosanase plays an important role on enzymatic production of chitosan oligosaccharides (COSs). The present study describes the gene cloning and high-level expression of a high efficiency chitosanase from Bacillus mojavensis SY1 (CsnBm). The gene encoding CsnBm was obtained by homologous cloning and the open reading frame of this gene is 837 bp in length, which encods a protein of 278 amino acid residues, including a potential signal sequence of 36 amino acid residues. The CsnBm was overexpressed in Pichia pastoris X33 and the maximum activity and total protein concentration were 6052 U/mL and 3.75 g/L, respectively, which were obtained in fed-batch cultivation in a 50 L bioreactor. The optimal temperature and pH of purified CsnBm were 55 ℃ and 5.5, respectively. Meanwhile, CsnBm was stable from pH 4.0 to 9.0 and 40 to 55 ℃. The purified CsnBm exhibited no activity to other substrates but chitosan, and the smallest substrate was chitotetraose. Furthermore, CsnBm exhibited high efficiency to hydrolyze different concentration of chitosan to produce COSs. The result of this study not only identifies a high efficiency chitosanase for preparation of COSs, but also casts some insight into the high level production of chitosanase in heterologous systems.